Populations of wild and feral reindeer in Siberia and Far East of Russia - Leonid M. Baskin; Frank L. Miller (Rangifer, 2007)
Identification and cataloging of discrete reindeer (Rangifer tarandus) populations in Siberia and the Far East of Russia has not been carried out. This prohibits accurate measures of population structure and dynamics that would allow more intensive management of this important renewable resource. To rectify the lack of information, an inventory was made that identifies 84 wild populations and 3 feral populations originating from domestic reindeer. This inventory summarizes the information available on the location, approximate population size, approximate range size, and occurrence by ecoregions and habitat types of each of those 87 reindeer populations. The 87 reindeer populations used a collective landmass of about 3 000 000 km2. The range size for each population was calculated to be between 446 km2 and 392 267 km2, with a mean ± SE of 34 033 ± 5734 km2. The 86 populations for which population size could be approximated totaled 790 655 reindeer, with an approximate mean ± SE of 9194 ± 2517, a minimum size of 50, and maximum size of 145 000. The location of the calving grounds could be determined for only 26 (30%) of the 87 reindeer populations.